Triple valve replacement on rheumatic heart disease patient: a case report - Haryo Aribowo; Yoga Arditya; Yosua Martin (Published by Universitas Gadjah Mada, 2024)
Triple valve replacement surgery is a complex, open-heart surgery to permanently replace all three heart valves (mitral, aorta, and tricuspid) in situations such as valvular diseases as complications of rheumatic heart disease. The expected outcome of the surgery is the proper functioning of the heart valves and the improvement of intracardiac blood flow. Triple valve replacement surgery is still considered a challenging procedure to be performed in developing countries including Indonesia due to its complexity and difficulties. The procedure needs a capable surgeon followed by the prolonged use of cardiopulmonary bypass machines and aortic cross-clamping procedures. This study presented the result of a successful triple valve replacement surgery on a 45 y.o. female with rheumatic heart disease who has manifested into cardiac valve complications. Follow-up examinations conducted directly after surgery, on the 1st, 8th postoperative day, and six months after discharge showed the desired outcome of well-functioning mechanical valves and normal global systolic function of the left ventricle, without significant postoperative cardiac events and complications. The result indicated that triple valve replacement surgery is a safe and effective procedure for rheumatic heart disease patients requiring surgical replacement of all three heart valves, encouraging more implementation of this procedure.